Unilateral Fusion of Two Primary Mandibular Teeth: Report of a Portuguese Archeological Case - Ana Maria Silva; Ana Leonor Silva (Dental Anthropology Association, 2007)
This paper describes a unilateral fusion of two mandibular teeth in an infant skeleton recovered from the late Roman cemetery of Miroiço (Sintra, Portugal). Morphological and radiographic data were used for the analysis and interpretation of this dental anomaly. A brief review of the literature of present day primary dental fusion is presented. This report shows that primary dental fusion was present in Portuguese past populations, representing a contribution to the history of dental anomalies.